2020
DOI: 10.4178/epih.e2020057
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trend and spatial distribution of acute lymphoblastic leukemia in Iranian children during 2006 -2014: A Mixed Ecological Study

Abstract: The most common type of childhood cancers is acute lymphoblastic leukemia (ALL). The present study was conducted to determine the spatial-temporal epidemiological status of ALL in Iran. METHODS: Using an exploratory mixed design, this ecological study examined 3769 under-15 children with ALL who were reported in the National Cancer Registry of Iran during 2006 to 2014. Data were analyzed using the Mann-Whitney U, Getis-Ord General G (GOGG), Optimized hot spot analysis (OHSA), and the Pearson correlation coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…This will show the output's best possible results to identify hot and cold spots. OHSA demonstrates results at 90%, 95%, and 99% confidence levels (24).…”
Section: Spatial Pattern Analysis and Cluster Identificationmentioning
confidence: 91%
See 2 more Smart Citations
“…This will show the output's best possible results to identify hot and cold spots. OHSA demonstrates results at 90%, 95%, and 99% confidence levels (24).…”
Section: Spatial Pattern Analysis and Cluster Identificationmentioning
confidence: 91%
“…In order to indicate more precise clusters of COVID-19 in the world, an optimized hot spot analysis (OHSA) was employed. This method, according to the Getis-Ord Gi*, with the optimization of distance band for determining hot and cold spots (24). Using incremental spatial correlation, OHSA automatically selects the optimal bandwidth value at which spatial autocorrelation and clustering intensity are maximum and then uses it as an analytical scale for the Getis-Ord Gi * statistic (24).…”
Section: Spatial Pattern Analysis and Cluster Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kuldorff's purely spatial scan statistic test and the Gini Optimized Cluster Collection method were used to detect the high-risk and low-risk clusters and estimate the relative risk of drug poisoning in any county of Semnan Province. This new method separates clusters on a more local scale and optimizes the radius of the circular scanning window for cluster detection, thereby demonstrating the best results in cluster detection (13,16,17).…”
Section: Methodsmentioning
confidence: 99%
“…The closer the value of the statistic is to +1, the more it is clustered, and the closer it is to -1, the more it is dispersed, Furthermore, if its value is zero, the spatial distribution of the phenomenon is random. The null hypothesis indicated that the distribution of drug poisoning was randomly dispersed in Semnan Province (13,16). The Kuldorff's purely spatial scan statistic test and the Gini Optimized Cluster Collection method were used to detect the high-risk and low-risk clusters and estimate the relative risk of drug poisoning in any county of Semnan Province.…”
Section: Methodsmentioning
confidence: 99%